Physical properties of full-ripe Dabai (Canarium odontophyllum Miq. variety Song) at different fractions - Abdul Rashid, Nur Afiqah Hani; Shamsudin, Rosnah; Ariffin, Siti Hajar; Zainol Abdullah, Wan Nor Zanariah; Megat Ahmad Azman, Puteri Nurain (Universiti Putra Malaysia Press, 2024)
Dabai fruit is an exotic and seasonal fruit in Sarawak. Among the varieties available, the Song variety was chosen due to better taste and high demand amongst local consumers. This study determined the physical properties of dabai (Song variety) at three different fractions: whole fruit, nut, and kernel. According to the results, whole fruit had the highest values in geometric mean diameter (27.86 mm), volume (12.70 cm3), mass (13.89 g), surface area (2442.60 mm2) and angle of repose (39.06°) when compared to nut and kernel. Bulk density of dabai nut reached the highest with the value of 0.63 gcm-3. Kernel had the highest percentage of porosity (80.50) compared to others. The correlations of physical properties between whole fruit, nut and kernel were further analysed using Principal Component Analysis (PCA). The findings can potentially be useful in the design of handling and processing equipment. © Universiti Putra Malaysia Press.